The times, they are a changing - Nicolino Ambrosino FERS (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
With the increasing life expectation and population age due to medical progress and better general lifeconditions, including among others nutrition and housing, patients’ clinical patterns are fast moving towardgreater complexity, multi-morbidity, comorbidity and chronic criticality.2 As a consequence health systemswill have to face increasing burden and different approaches compared to the past.At the same time in relatively few years Respiratory Rehabilitation has become a corner stone of comprehensivemanagement of Chronic Obstructive Pulmonary Disease (COPD) and, with less but increasing evidence, ofother respiratory and non respiratory diseases. The positive effects on symptom control, ability to cope withactivity of daily life and on quality of life are unquestioned and we don’t need any more randomised studieson these outcome measures in COPD patients. We need more studies on survival in COPD and on the otheroutcome indexes of diseases other than COPD.3Nevertheless to face the above changes, the present mean skills and training processes are not enough anymore. Also Rehabilitation clinicians and physiotherapists, while maintaining their present and historicalskills, must change their approach and add new competences along these lines at least:1. A comprehensive approach to the patients, moving from “disease-centered” to “patient-centered”paradigm of care.4 This task requires by cares a cultural revolution and an effort to improve andenlarge personal knowledge. In other words we have to face a greater effort to improve skills andtraining involving at the same time deeper and wider fields of knowledge and intervention in diseasesother than COPD and in patients with comorbididites with special attention to the most prevalentdiseases in each country like TB.52. Greater ability in facing the needs of “chronically critical” patients. This task requires skills in longtermcritical conditions like the effects of the so called “ICU induced neuro-myopathy” and relatedcognitive problems.63. A greater involvement in end-of-life and palliative care requiring abilities to be part of teams facingethical issues. This task requires a new approach to diseases including a deeper involvement inempathy with patients in the frame of the religious habits and traditions of each society.7“Nomina sunt consequential rerum”,8 therefore in the light the above issues, we should not speak about“Pulmonary Rehabilitation” anymore, but rather about “Rehabilitation of patients with (also) respiratoryproblems”. In the present Issue of IJPMR several qualified authors deal with this new approach, reporting dataon Rehabilitation in diseases other COPD, opening a window on the future developments of Rehabilitation.Nicolino Ambrosino FERSResearch Director and Director of Respiratory Department, Rehabilitation and Weaning CentreAuxilium Vitae, Volterra, Italy